HEV in Blood Donors in Switzerland: The Route to Safe Blood Products - Mauro Serricchio; Peter Gowland; Nadja Widmer; Martin Stolz; Christoph Niederhauser (Pathogens, 2024)
The hepatitis E virus (HEV) is an emerging infectious disease with zoonotic potential, causing acute hepatitis in humans. Infections in healthy individuals are often acute, self-limiting and asymptomatic, thus leading to the underdiagnosis of HEV infections. Asymptomatic HEV infections pose a problem for blood transfusion safety by increasing the risk for transfusion-transmitted HEV infections. Here, we describe the journey from determining the HEV seroprevalence among blood donors to the implementation of routine HEV RNA testing of all blood products in Switzerland in 2018 and summarise the HEV cases detected since. In total, 290 HEV-positive blood donations were detected by mini-pool nucleic acid testing (NAT) in Switzerland in the period of October 2018–December 2023, equal to an incidence of 20.7 per 100,000 donations. Thanks to the implemented scheme, no transfusion-transmitted infections occurred in this period. Furthermore, blood donation monitoring has proven to be an effective means of detecting HEV outbreaks in the general population. HEV cases in Swiss blood donors are caused by two major genotypes, the Swiss-endemic subtypes 3h3 and 3c. Interestingly, 11 HEV cases (5%) were of genotype 3ra, a variant found in wild and farmed rabbits. Our results indicate that mini-pool NAT is an efficient method to reduce the risk of transfusion-transmitted HEV infections.